2002
DOI: 10.1002/jsfa.1044
|View full text |Cite
|
Sign up to set email alerts
|

The effect of digesta sampling time and dietary protein source on ileal nitrogen digestibility for the growing rat

Abstract: The effect of time that digesta were collected on the quantity and representativeness of ileal digesta and on the determination of apparent and true ileal nitrogen (N) digestibility for growing rats was investigated. Semi‐synthetic diets containing chromic oxide as an indigestible marker were given to 200 g live weight rats for 8 days as a single daily meal. The experimental treatments comprised six diets (lactalbumin, soy protein isolate, wheat gluten, fish, protein‐free (PF), enzymically hydrolysed casein (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…This agrees with the results observed by Butts et al [3] when ileal N digestibility of wheat gluten was compared with fish meal, lactalbumin and soy protein isolate. Ammonia-N concentration in digestive contents might be considered as an index of microbial deamination and therefore reduced the amino acid availability for absorption in the small intestine.…”
Section: Wheat Gluten Vs Lt Fish Mealsupporting
confidence: 93%
“…This agrees with the results observed by Butts et al [3] when ileal N digestibility of wheat gluten was compared with fish meal, lactalbumin and soy protein isolate. Ammonia-N concentration in digestive contents might be considered as an index of microbial deamination and therefore reduced the amino acid availability for absorption in the small intestine.…”
Section: Wheat Gluten Vs Lt Fish Mealsupporting
confidence: 93%
“…The present study, by virtue of the flexibility in its design, gave the opportunity to determine whether food dry matter intake would affect the endogenous flow of amino acids at the terminal ileum. Earlier work had shown that a meal feeding regimen was suitable for obtaining representative samples and the measurement of endogenous amino acid flows 6. 13 The procedure adopted for this study, which was based on a meal feeding regimen, was successful in obtaining a range of food dry matter intakes.…”
Section: Discussionmentioning
confidence: 99%
“…On day 15, at the completion of the experimental feeding period, the rats were rendered unconscious by asphyxiation in carbon dioxide gas and then killed by decapitation. Rats were killed 3 h after the food pots were placed in the cages to start the meal feeding period 6. On the final day the times of placing food in the cages were staggered to enable the ileal digesta samples to be collected within 20 min of the predetermined elapsed interval.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty experimental diets were formulated to each contain 100 g/kg protein, such that each cat food was the sole source of protein in the respective diet. The respective inclusion rates for the 20 cat foods (diets [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] were 236, 221, 235, 172, 217, 215, 224, 295, 224, 216, 287, 411, 350, 293, 342, 260, 285, 308, 340, and 243 g/kg. Other dietary ingredients were 50 g/kg purified cellulose, 100 g/kg sucrose, 50 g/kg soybean oil, 50 g/kg proprietary vitamin mix, and 50 g/kg proprietary mineral mix.…”
Section: Methodsmentioning
confidence: 99%